2015
DOI: 10.1016/j.bbmt.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of Natural Killer Cells in Intravenous Immunoglobulin–Induced Graft-versus-Host Disease Inhibition in NOD/LtSz-scidIL2rg−/− (NSG) Mice

Abstract: Although clinical studies have yet to demonstrate clearly the use of intravenous immunoglobulin (IVIG) for prevention of graft-versus-host disease (GVHD), their effective use in a xenogeneic mouse model has been demonstrated. We aimed to determine the mechanism of action by which IVIG contributes to GVHD prevention in a xenogeneic mouse model. NOD/LtSz-scidIL2rg(-/-) (NSG) mice were used for our xenogeneic mouse model of GVHD. Sublethally irradiated NSG mice were injected with human peripheral blood mononuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…Humanized mice have been widely used to model human immune cell function in vivo (1)(2)(3)(4)(5)(6). In the Hu-PBL-SCID model, a major limitation of studying human T-cell function is the rapid development of fatal xenogeneic GVHD that not only shortens the experimental time window but also confounds the analysis of human T cell function due to the underlying ongoing acute GVHD that eventually kills the mice (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In the present study, we have overcome this limitation by eliminating expression of murine MHC class I and II in NSG mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humanized mice have been widely used to model human immune cell function in vivo (1)(2)(3)(4)(5)(6). In the Hu-PBL-SCID model, a major limitation of studying human T-cell function is the rapid development of fatal xenogeneic GVHD that not only shortens the experimental time window but also confounds the analysis of human T cell function due to the underlying ongoing acute GVHD that eventually kills the mice (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In the present study, we have overcome this limitation by eliminating expression of murine MHC class I and II in NSG mice.…”
Section: Discussionmentioning
confidence: 99%
“…The Hu-PBL-SCID model has been used to study human infectious agents, tissue transplantation, and human T-cell immune function (2,(12)(13)(14). One of the primary uses of this model is the study of acute graft-versus-host disease (GVHD) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), a major problem in clinical hematopoietic stem cell transplantation (26). NSG mice engrafted with human PBMCs develop an acute xenogeneic GVHD-like disease upon recognition of the murine cells and tissues by mature human T cells (23).…”
mentioning
confidence: 99%
“…This limited binding to rat B cells suggests that GL-2045 may not bind to the inhibitory FcγRIIb receptor on the surface of circulating immune cells in the rat. Similarly, based on recent studies demonstrating that NK cells are required for the IVIG-mediated prevention of graft vs. host disease (GVHD) in a mouse model, the inability of GL-2045 to engage rat NK cells may also contribute to the different GL-2045-mediated cytokine changes observed in NHPs vs. rats (48).…”
Section: Discussionmentioning
confidence: 99%
“…Chong et al [60] recently demonstrated that the beneficial effect of IVIG in mice with EAE was absolutely dependent on NK cells and that the upregulation of Treg cells, which is associated with the IVIG-induced EAE disease amelioration, was also dependent on the presence of NK cells in the mice. Furthermore, Gregoire-Gauthier et al [61] reported that in SCID mice during xenogenic graft vs. host disease including with IVIG, resolution of NK cell deficits have been observed [30,[62][63][64][65][66][67][68][69]. Whether this is related to IVIG potentiation of the effects of certain cytokines on NK cells remains to be determined in humans receiving IVIG therapy, and these studies are currently being initiated.…”
Section: Accepted Manuscriptmentioning
confidence: 96%